PENGEMBANGAN BUKU AJAR SASTRA ANAK BERBASIS BUDAYA LOKAL - Puspitasari, Dhika; Furinawati, Yunita; Huda, Muhamad Binur (IKIP PGRI MADIUN, 2016)
As one kind of literature, childrens literature has a mission to introduce the world of literature to children from an early age. Childrens literature puts the viewpoint of children at the center of storytelling. However, it is not impossible if another mission also included the works of childrens literature. Childrens literature can be used as a means to teach the values of life, example and culture. So, teaches childrens literature directly or indirectly two things at once, or even more. In the simplicity of childrens literature stored complex dimensions. In addition, childrens literature can also be used as a means to introduce the local culture to children. Childrens literature-based local culture seeks to instill a love of cultural values that are around them. Unfortunately, Language and Literature Education curriculum Indonesia have not been up to elaborate teaching this genre. The course of childrens literature is not supported by adequate instructional media. This research aims to develop childrens literature-based instructional media for student PBSI IKIP PGRI Madiun.As one kind of literature, childrens literature has a mission to introduce the world ofliterature to children from an early age. Childrens literature puts the viewpoint of children at thecenter of storytelling. However, it is not impossible if another mission also included the works ofchildrens literature. Childrens literature can be used as a means to teach the values of life,example and culture. So, teaches childrens literature directly or indirectly two things at once, oreven more. In the simplicity of childrens literature stored complex dimensions. In addition,childrens literature can also be used as a means to introduce the local culture to children.Childrens literature-based local culture seeks to instill a love of cultural values that are aroundthem. Unfortunately, Language and Literature Education curriculum Indonesia have not been upto elaborate teaching this genre. The course of childrens literature is not supported by adequateinstructional media. This research aims to develop childrens literature-based instructional mediafor student PBSI IKIP PGRI Madiun